2016
DOI: 10.3847/1538-4357/833/1/104
|View full text |Cite
|
Sign up to set email alerts
|

Spitzer Observations of Long-Term Infrared Variability Among Young Stellar Objects in Chamaeleon I

Abstract: Infrared variability is common among young stellar objects, with surveys finding daily to weekly fluctuations of a few tenths of a magnitude. Space-based observations can produce highly sampled infrared light curves, but are often limited to total baselines of about 1 month due to the orientation of the spacecraft. Here we present observations of the Chameleon I cluster, whose low declination makes it observable by the Spitzer Space Telescope over a 200-day period. We observe 30 young stellar objects with a da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 118 publications
7
22
1
Order By: Relevance
“…This is similar to what is inferred from observations (e.g. Scholz et al 2013;Hillenbrand & Findeisen 2015;Fischer et al 2019) (see also Peña et al 2019, for longer outburst timescale estimates for older, Class I/II, YSOs). It is assumed that in the quiescent phase gas accretes onto the protostar at a rate oḟ M = 10 −6 M yr −1 (this is a free parameter in our calculation) and the protostellar luminosity is then on the order of ∼ 1 L .…”
Section: Radiation Hydrodynamic Simulationssupporting
confidence: 89%
See 1 more Smart Citation
“…This is similar to what is inferred from observations (e.g. Scholz et al 2013;Hillenbrand & Findeisen 2015;Fischer et al 2019) (see also Peña et al 2019, for longer outburst timescale estimates for older, Class I/II, YSOs). It is assumed that in the quiescent phase gas accretes onto the protostar at a rate oḟ M = 10 −6 M yr −1 (this is a free parameter in our calculation) and the protostellar luminosity is then on the order of ∼ 1 L .…”
Section: Radiation Hydrodynamic Simulationssupporting
confidence: 89%
“…These flux increases happen on a timescale of decades to centuries. The authors note that although the continuum flux increases are smaller than observed in classical FUOrs, the variability found in their models is larger than currently observed for non-eruptive young protostars (Rebull et al 2015;Flaherty et al 2016;Rigon et al 2017). The variability of their models is also larger than that found by the TRANSIENT Survey (Mairs et al 2017;Johnstone et al 2018;Mairs et al 2018), which reports secular changes of order 5-10% per year from about 10% of the protostars bright enough to get good measurements.…”
Section: Introductionmentioning
confidence: 80%
“…Abramowicz et al (1992) suggested that vortices in hot accretion disks may explain the variability in their X-ray temporal power spectra. Similar temporal variability is observed in young stellar objects (Flaherty et al 2016), which may also be caused by vortices.…”
Section: Dynamical Interaction Of Vortices In a Protoplanetary Disksupporting
confidence: 73%
“…Jensen et al (2007) found a periodicity in the optical light curve of UZ Tau E which matched the orbital period, however the flux variations were much slower with low amplitude, and direct accretion probes such as Hα showed inconclusive correlations. Three protostellar objects have also been found to exhibit periodic infrared brightenings that look very much like pulsed accretion (Muzerolle et al 2013;Hodapp & Chini 2015;Flaherty et al 2016), although no evidence of binarity has yet been published.…”
Section: Introductionmentioning
confidence: 99%